Introduction of telepharmacy medication review by the telecare research interest group for Airlangga Nexus students: Serumpun 2025 - Karuppannan, Mahmathi; Ismail, Farhana Fakhira; Nik Mustaffa Shapri, Nik Aishah Najwa; Ibrahim, Norkasihan; Zulkifly, Hanis Hanum; Mohd Noordin, Zakiah; Ibrahim, Noorizam (Faculty of Pharmacy, 2025)
The Telehealth and Remote Patient Care (TeleCare) Research Interest Group (RIG), established in February 2025 and led by Assoc. Prof. Dr. Mahmathi Karuppannan, consists of nine active members. One of the group’s primary goals is to train future pharmacists and other allied health professionals in digital health, with a particular focus on enhancing patient care through telehealth. The RIG is dedicated to advancing digital health through a multidisciplinary approach, bringing together experts from pharmacy, nursing, computer science, and mathematics across multiple campuses, all of whom are driven by a shared passion for digital health.